2017
DOI: 10.1016/j.neubiorev.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The sleep phenotype of Borderline Personality Disorder: A systematic review and meta-analysis

Abstract: There were few significant differences between BPD and clinical (majority depressed) control groups. Conclusion:BPD is associated with comparable sleep disturbances to those observed in depression. These disturbances are not solely attributable to comorbid depression. Given growing evidence that sleep disturbance may exacerbate emotional dysregulation and suicide risk, treatments for BPD should explicitly address sleep problems. Future studies should utilise prospective designs to ascertain whether (and in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 75 publications
5
45
3
Order By: Relevance
“…Previous sleep investigations in BPD have used polysomnography, with a view to comparing BPD with mood disorder. Thus, a recent systematic review of the relevant literature highlighted the reduced sleep quality in BPD compared with healthy samples and the overlap with reported abnormalities in patients with mood disorder 8 . It correctly identified sleep disorder as a broadly neglected element of the management in BPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous sleep investigations in BPD have used polysomnography, with a view to comparing BPD with mood disorder. Thus, a recent systematic review of the relevant literature highlighted the reduced sleep quality in BPD compared with healthy samples and the overlap with reported abnormalities in patients with mood disorder 8 . It correctly identified sleep disorder as a broadly neglected element of the management in BPD.…”
Section: Discussionmentioning
confidence: 99%
“…BPD resembles BD in that patients experience mood instability, but this variability of mood is greater 6 . Descriptions of sleep difficulties in BPD refer quite non-specifically to insomnia 8 . The BPD group were a relevant control group because the diagnoses are sometimes confused even though heritability and the clinical course are different from BD.…”
Section: Introductionmentioning
confidence: 99%
“…There is little or no previous relevant research in BPD. The most recent meta-analytic review of the literature examining sleep disturbance primarily identified acute polysomnography (PSG) recordings which are limited to single nights (30). These findings describe greater sleep onset latency, poor sleep efficiency and shorter sleep duration in BPD compared with controls (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the association between sleep disturbances and suicidal ideation may be potentiated by Borderline Personality Disorder (BPD; Winsper & Tang, 2014;Winsper et al, 2017). Previous work, however, has returned contradictory results (e.g., Oltmanns & Oltmanns, 2015), and the temporal, within-person link of sleep and suicidal ideation in BPD has received limited clinical and research attention (Winsper & Tang, 2014; see Liu et al (2020) for a recent systematic review and meta-analysis of longitudinal studies).…”
Section: Sleep and Next-day Negative Affect And Suicidal Ideation In mentioning
confidence: 99%